Plato’s The Republic recovered. A few ethical, economic and social aspects in contemporary dialogues - Głodowska, Anna; Matera, Paulina; Matera, Rafał (Annales. Etyka w Życiu Gospodarczym, 2019)
The main purpose of the article is the presentation and interpretation of some ethical, economic and social aspects in the works of Plato. The division of labour, wealth, the meaning of money, use of interest and paying taxes are the most interesting problems in Plato’s vision of The Republic. There one can also find some current problems such as the attitude of citizens towards their states, the ethical standards required of the authorities or the role of women. This article was written in the form of a dialogue; the same as the works of Plato.